Cyclooxygenase-2 Induced the β-Amyloid Protein Deposition and Neuronal Apoptosis Via Upregulating the Synthesis of Prostaglandin E(2) and 15-Deoxy-Δ(12,14)-prostaglandin J(2) - Guan, Pei-Pei (Neurotherapeutics, 2019)
Elevated levels of cyclooxygenase-2 (COX-2) and prostaglandins (PGs) have been shown to be involved in the pathogenesis of Alzheimer’s disease. Analysis of the underlying mechanisms elucidated a function of sequential PGE(2) and PGD(2) synthesis in regulating β-amyloid protein (Aβ) deposition by modulating tumor necrosis factor α (TNF-α)-dependent presenilin (PS)1/2 activity in COX-2 and APP/PS1 crossed mice. Specifically, COX-2 overexpression accelerates the expression of microsomal PGE synthase-1 (mPGES-1) and lipocalin-type prostaglandin D synthase (L-PGDS), leading to the synthesis of PGE(2) and 15-deoxy-Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) in 6-month-old APP/PS1 mice. Consequently, PGE(2) has the ability to increase Aβ production by enhancing the expression of PS1/2 in a TNF-α-dependent manner, which accelerates the cognitive decline of COX-2/APP/PS1 mice. More interestingly, low concentrations of 15d-PGJ(2) treatment facilitate the effects of PGE(2) on the deposition of Aβ via TNF-α-dependent PS1/2 mechanisms. In contrast, high concentrations of 15d-PGJ(2) treatment inhibit the deposition of Aβ via suppressing the expression of TNF-α-dependent PS1/2. In this regard, a high concentration of 15d-PGJ(2) appears to be a therapeutic agent against Alzheimer’s disease. However, the high 15d-PGJ(2) concentration treatment induces neuronal apoptosis via increasing the protein levels of Bax, cleaved caspase-3, and DFF45, which further impairs the learning ability of APP/PS1 mice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-019-00770-z) contains supplementary material, which is available to authorized users.